Genotype-phenotype correlation in Brazillian Rett syndrome patients - Lima, Fernanda Teresa de [UNIFESP] (2009)
BACKGROUND: Rett syndrome (RS) is a severe neurodevelopmental X-linked dominant disorder caused by mutations in the MECP2 gene. PURPOSE: To search for point mutations on the MECP2 gene and to establish a correlation between the main point mutations found and the phenotype. METHOD: Clinical evaluation of 105 patients, following a standard protocol. Detection of point mutations on the MECP2 gene was performed on peripheral blood DNA by sequencing the coding region of the gene. RESULTS: Classical RS was seen in 68% of the patients. Pathogenic point mutations were found in 64.1% of all patients and in 70.42% of those with the classical phenotype. Four new sequence variations were found, and their nature suggests patogenicity. Genotype-phenotype correlations were performed. CONCLUSION: Detailed clinical descriptions and identification of the underlying genetic alterations of this Brazilian RS population add to our knowledge of genotype/phenotype correlations, guiding the implementation of mutation searching programs.